Quality of health care perceived by users in Catalan prisons - L García-González; J Mendioroz-Peña; B Armenteros-López; N Sole-Zapata; P Alonso-Gaitón; E Cuadro-Pena (Sociedad Española de Sanidad Penitenciaria, 2021)
Abstract Objectives To describe inmates' perceptions of healthcare quality in Catalonian prisons. Material and method Transversal study of 6,856 inmates in Catalan prisons in September 2017. Randomized simple screening was used to randomly distribute 1,048 polls in which different aspects of perceived quality of healthcare were evaluated. The results were also categorized according to age, sex, time spent in prison, background and academic levels. We also analysed the differences between results in healthcare quality according to socio-demographic variables. Results 84.87% of patients show satisfaction with the quality of healthcare received. Women are more satisfied with consultations than men (OR: 2.04; p = 0.009). Patients with a higher educational level are less satisfied than those with a lower educational level, with significant differences in 11 of the 14 items. Those over 65 years of age were more satisfied than the rest in 11 of the 14 items evaluated. Foreign patients were more satisfied than Spanish inmates in time flexibility (OR: 0.69; p = 0.018) and in waiting times for visits (OR: 0,63; p = 0.006), whereas they are less satisfied with the healthcare professionals' image (OR: 1.97; p = 0.03). Discussion Noteble features of our study include the fact that although global satisfaction is high, some dimensions, like reliability, could improve. The results were submitted to the General Directorate to enable more in-depth study of the variables where there is less satisfaction and to design further improvements.